KAJIAN KINERJA PENYULUH PERTANIAN PADA BALAI PENYULUHAN PERTANIAN (BPP) PRAFI DI KABUPATEN MANOKWARI - Mei Sanadila Halid; Meky Sagrim; Sombuk Musa Yosep (Sosio Agri Papua, 2021)
ABSTRACT The development of the agricultural sector, especially food crops, in Manokwari district, supported by an extension system which is institutionally under the coordination and management of the Agricultural Extension Center under the Manokwari District Agriculture Office. The extension activities are managed by the Agricultural Extension Center (BPP), as many as 4 Balai, namely Masni, Prafi, Warmare, and Manokwari. These four BPPs are supported by 88 Field Agricultural Extension Workers (PPL). Currently, the Manokwari Regency Agricultural Extension Center is in charge of coordinating and fostering 4 BPPs in Manokwari Regency, namely, BPP Masni, BPP Prafi, BPP Warmare and BPP Manokwari. This study aims to assess the existing condition of BPP Prafi, evaluate the performance of PPL in WKBPP Prafi, identify factors that affect the performance of PPL. This research took place from 06 July 2021 to 05 August 2021. The place of implementation was at (WKBPP) at BPP Prafi, Manokwari Regency. The method used is descriptive method. The subjects in this study were PPL at (WKBPP) Prafi. The sampling method is by census. The data collected are primary and secondary data. Data analysis was done by tabulation with a frequency distribution to assess PPL performance, while to find out the factors related to PPL performance were analyzed using tabular analysis. Based on the results of research that has been carried out in Prafi, Manokwari Regency. The performance of field agricultural extension workers in Prafi, Manokwari Regency, was declared in the good category. This is supported by three indicators as parameters, namely indicators of extension programs, implementation of agricultural extension, evaluation and reporting. PPL in Prafi has implemented an extension program, compiling a work schedule in which joint visits with extension workers and field visits must be at the invitation of the farmers. In addition, the extension workers have applied the principle of learning while working because the PPL's job is not only to be a lecturer but also to go out in the field to help the fostered farmers carry out planting, harvesting and selling. The factors that influence the success or failure of PPL are success factors, namely education level, age, and length of work. Keywords: PPL Performance